Karakteristik Serat Kulit Waru Yang Disusun Laminasi Bermatrik Polyester Dengan Orientasi Serat (30ᴼ,35ᴼ,40ᴼ) Terhadap Sifat Fisis Dan Mekanis - SISWANTO, DWI; , Ir. Bibit Sugito, MT; , Ir. Ngafwan, MT (2016)
Research hibiscus bark fiber composite rod is intended to describe the physical and mechanical properties of skin stem hibiscus fiber composites due to variation of the angle and macro photographs describe fiber composite skin stem hibiscus after testing tensile and izod impact testing due to variations in the angle. Beginning the process of cutting the bark of the hibiscus tree trunk immersion was continued for 1 month.Next hibiscus bark peeling process and sistem fibers taken 2 layers of skin.Clean water rinse aid.The drying under the sun to dry subsequent immersion process KMnO4 5% per 1 liter of distilled water for 2 hours.The drying in the sun until dry and continue the process of oven until the moisture content of 10 PPM. Composite manufacturing is done by hand lay - up method,fiber ratio 30%,fiber orientation [-300 /300];[-350 / 350];[-400 / 400]. Using polyester resin series BQTN 157. As for the process of testing is test ASTM D3039-07 stadart tensile and impact testing using standrd ASTM D256-03 with the variation of the angle 300, 350, 400,and describe the tensile strenght,impact prices and the macro image composite polyester fiber trunk . Tensile test results on a composite prepared symmetry [-300/300],[-350/350],[-550/550] the maxsimum tensile strenght contained in the composite with a test corner 300 , where the strenght of its increase in the amount of 54.645N/mm2 is large than the composite with a test corner 350,amounting 37,105 N/mm2 and 400,amounting 20,395 N/mm2. Whereas the izod impact testing of composites prepared symmetry [-300/300 ],[-350350],[-400/400] composites with a test corner 300,which energy is absorbed and impact prices increased by 2,534 J and 0,00434 J/mm2 greter than the composite with a test corner 350 is equal 2,346 J and 0,00402 J/mm2,the test angle 400 is equal to 2,275 J and 0,00390 J/mm2. The macro image tensile test specimens fault structure composite bumpy and irregular.At an angle of 400 trials going on the enlargement process void and pull out the fiber is dominating .Whereas the macro image izod impact testing results of composite fault structure on 300 test specimens seen that the pull - out of fiber .